2004
DOI: 10.1097/01.brs.0000143619.34308.b4
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention for the Management of Acute Low Back Pain

Abstract: At short-term, intervention is more effective than advice on staying active, leading to more rapid improvement in function, mood, quality of life, and general health. The timing of intervention affects the development of psychosocial features. If treatment is provided later, the same psychosocial benefits are not achieved. Therefore, an assess/advise/treat model of care seems to offer better outcomes than an assess/advise/wait model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(50 citation statements)
references
References 20 publications
3
47
0
Order By: Relevance
“…The distribution of the variable symptom duration (number of days) appeared non-normal and was converted into both dichotomous and ordinal scales. Six weeks (45 days) was used as the threshold to dichotomize symptom duration (acute ≤ 6 weeks, chronic > 6 weeks) based on previous literature (Fritz et al, 2007b, 2008; van Tulder et al, 2006; Wand et al, 2004). Four demographic and history variables (Table 2) and seven physical examination variables (Table 3) were found to be correlated to one-week change in LM thickness (r pbis = −0.41 to 0.18, p < 0.15).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the variable symptom duration (number of days) appeared non-normal and was converted into both dichotomous and ordinal scales. Six weeks (45 days) was used as the threshold to dichotomize symptom duration (acute ≤ 6 weeks, chronic > 6 weeks) based on previous literature (Fritz et al, 2007b, 2008; van Tulder et al, 2006; Wand et al, 2004). Four demographic and history variables (Table 2) and seven physical examination variables (Table 3) were found to be correlated to one-week change in LM thickness (r pbis = −0.41 to 0.18, p < 0.15).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few instruments were specific to single health disciplines, or single persistent pain constructs. The publication of assessment instruments appears to mirror developments in under-standing persistent pain behaviors and presentations, in terms of neuroanatomy, biology, physiology, psychology, and social science 514. However, no one instrument currently appears to assess all features of persistent pain, and thus multiple instruments are required to provide a comprehensive description of an individual with persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that early identification of patients at-risk of developing persistent pain reduces disability and increases return-to-work rates 914. This paper reports on a systematic literature review that identified and critically appraised assessment instruments for persistent pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence that early intervention in general, and early treatment by physiotherapists in particular, for common musculoskeletal problems such as low back pain can reduce the amount of time people are off sick and can help to prevent acute problems from becoming chronic [5,44-46]. Although early intensive treatment is not always beneficial for recovery in musculoskeletal injuries [47], services that ensure timely access to care for musculoskeletal pain contribute importantly to patient experience and satisfaction [48].…”
Section: Arguments For Considering Other Models Of First-contact Carementioning
confidence: 99%